The physician as person framework: How human nature impacts empathy, depression, burnout, and the practice of medicine - Liao, Lester (Canadian Medical Education Journal, 2017)
Troubling trends of depression, burnout, and declines in empathy have been demonstrated amongst residents. I argue that while interventions in medical education are helpful, a new perspective on the issue requires a more fundamental understanding of this problem. Rather than training physicians to act in certain ways, we must first recognize that physicians are first and foremost people. This core principle forms the basis of the framework that educators can use to help learners. Five areas of humanity with implications for physicians are discussed: 1) Physicians and patients share their humanity; 2) People are self-integrated in both personal and professional lives; 3) People are dynamic, thoughtful, and emotional; 4) People are finite; and 5) People are moral beings. Recognizing these can mitigate various factors contributing to current struggles. I also discuss practical implications of this framework to help residents flourish.